A gaming approach to networked infrastructure management. Issue 7 (3rd July 2017) - van Riel, Wouter; Post, Johan; Langeveld, Jeroen; Herder, Paulien; Clemens, François
Abstract: Operational decision-making processes for networked infrastructure management often occur as a multi-actor planning problem, implying these are based on negotiations between different stakeholders in addition to available system quality information. As such, does more accurate data about actual structural condition lead to other or better decision-making? A serious game is introduced, Maintenance in Motion, aiming at investigating the influence of information quality on rehabilitation decisions, for single- and multi-actor decision-making. Players manage drinking water, gas, sewer and street infrastructures. They are to balance their individual goal, cost-effectiveness, with their team utility, increasing overall infrastructure quality to minimise failure while minimising overall public costs. The game design, calibration and solution space are presented.